IMPLEMENTASI METODE ACCELERATED LEARNING DALAM PEMBELAJARAN MATEMATIKA UNTUK MENINGKATKAN KEMAMPUAN PENALARAN MATEMATIS SISWA SMA - Fitriani, Meida; Mahuda, Isnaini (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2024)
This study aims to: (1) examine the differences in the improvement of mathematical reasoning abilities between students who receive instruction using the Accelerated Learning method and those who receive instruction using conventional methods; (2) determine students' responses to mathematics instruction using the Accelerated Learning method. The research method employed is a quasi-experimental method with a non-equivalent control group design. This study was conducted in one of the public high schools in Cimahi, involving tenth-grade students during the 2010/2011 academic year. The instruments used included instructional tools such as syllabi, lesson plans, and student worksheets; and data collection instruments such as mathematical reasoning ability tests, observation sheets, student daily journals, and questionnaires. The results of the study indicate that (1) there are differences in the improvement of mathematical reasoning abilities between students who received instruction using the Accelerated Learning method and those who received instruction using conventional methods. Furthermore, it can be stated that the improvement in mathematical reasoning abilities of students who received mathematics instruction through the Accelerated Learning method is higher than that of students who received mathematics instruction through conventional methods; (2) most students responded positively to mathematics instruction using the Accelerated Learning method.